DD-010 Online availability of oncology drugs affected by shortages. (24th February 2014) - Fittler, A; Vida, R; Rádics, V; Botz, L
Abstract : Background: There has been a sharp rise in the number of drug shortages during the past few years and they present a daily challenge for hospitals worldwide. According to the EAHP survey carried out in 2013 99% of hospital pharmacists have experienced problems with medicine supplies. Shortage issues are typical in the area of oncology. Currently numerous antineoplastic agents are frequently unavailable and delays in treatment have their consequences. Inaccessibility and the growing demand for necessary medicines increases the demand to purchase them outside the traditional supply chain. Thus, patients more and more often obtain these drugs from unreliable online suppliers. Due to ineffective international legislation and law enforcement illegitimate online medicines are a serious safety problem. Purpose: To survey the online availability of oncology drugs during shortages and to assess the indicators of patient safety hazards (no prescription requirement, illegitimacy of vendors and lack of product information). Materials and methods: We tested how easily patients could access out-of-stock oncology drugs online. We documented the characteristics of online vendors, prescription requirement, contact and product information, the drug prices, and the legitimacy of the sellers. As there are no European data on drug shortages, we looked at the official drug shortage list of the Hungarian National Institute of Pharmacy, which may also represent the shortages experienced in Europe. We searched with Google for the English and Hungarian terms of 43 products, including 16 antineoplastic agents (ATC L01) in October 2013. Results: Of the 16 antineoplastic agents, 15 (93.8%) were available online. A total of 121 web links were examined, including internet pharmacies, intermediary sites (n = 26) and social media links (n = 36). Oncology drugs were marketed by 31 internet pharmacies, nearly half (n = 14, 45.2%) of these were classified as illegitimate ("rogue") by LegitScript internet pharmacy verification standards. Numerous vendors offered multiple drugs in short supply for sale; significant (occasionally ten-fold) differences in drug prices were observed. In 72.2% of the cases no prescription was required. The medical information on the effects, dose and side effects was typically incomplete or missing. Only a small proportion of the patients (n = 5, 16.1%) were offered the opportunity to consult with healthcare professionals. The contact information of the vendor was often (n = 11) concealed. Conclusions: Patients can easily purchase most scarce anti-cancer drugs online without prescription. The lack of expert advice and unreliable information during this type of procurement pose great risks to patients' health. During the management of today's shortage crisis health professionals need to proactively highlight the dangers of illegitimate online drug sources. No conflict of interest.